Penerapan Pendidikan Agama Islam dalam Keluarga Broken Home di Desa Panisihan Kecamatan Maos Kabupaten Cilacap - Setya Murti; Donny Khoirul Aziz (DIMAR: Jurnal Pendidikan Islam, 2022)
Islamic Religious Education should have been taught by parents to children from an early age. Parents play an important role in teaching Islamic religious education because with this education children will know what teachings must be learned. Islamic religious education is also important to be applied in families who experience broken home. Affected children broken home from their parents it is prioritized to be given Islamic religious education because this religious education will later become a way of life for children. The purpose of this study was to find out how the application of Islamic religious education in the family-broken home in Panisihan Village, Maos District, Cilacap Regency. The type of research used is field research. Data collection techniques using the method of observation, interviews, and documentation. While the data analysis techniques used are data reduction, data presentation, and data verification. The results of the study show that the application of Islamic religious education in the family-broken home is indispensable. Various methods are used by parents to apply Islamic religious education to their children, such as: ordering the Koran to be recited at the Pondok or TPQ, teaching prayers, setting good examples and examples, and memorizing prayers and even hadiths.